Improving Prayer Skills By Using Demonstration Method in Grade IV B SDN 15 Sitiung: Peningkatan Keterampilan Sholat Dengan Menggunakan Metode Demonstrasi di Kelas IV B SDN 15 Sitiung - Suzanna kurniawati (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2020)
This research aims to improve the prayer skills of Grade III students of SDN 15 Sitiung through demonstarasi method of the year 2019/2020. The incapable of students to perform prayer movements properly and not memorize the students of prayer reading, so the authors are interested in carrying out research terhdapat learning prayer using demonstarasi method. This method of demonstarasi is a new innovation carried out in this school. By praying repeatedly, students perform prayer movements or in reciting the recitations in prayer. Because prayer is not just a movement, the reading must also be read correctly. So researchers used the way to recite prayer readings over and over again and loudly. It is hoped that reading aloud can be detected when reading incorrectly and justified. So the mistakes are quickly resolved. The collected research data is analyzed in a way: (1) the average value of pre-cycle results, cycle I, and cycle II compared overall. (2) The average score of the student's prayer practice test results, both from movement and reading, is compared to see if there is an increase in the practice results of the cycle per cycle. The application of demonstarasi method can improve the prayer skills of grade III students of SDN 15 Sitiung in the 2018/2019 school year. Results obtained in the pre cycle averaged 69.8 with a complete rate of 18%. In cycle I the average value is 73.9 with a completeness rate of 43%. In cycle II the average value is 80.0 with a completeness rate of 89%.